Can Spot Urine Protein Creatinine Ratio be an alternative for the 24 Hour Urine Protein to estimate proteinuria in Chronic Kidney Disease? A com-parative observational study - Raghavendra B L; Varsha R Mokhasi (Journal of Clinical and Biomedical Sciences)
Background: The definition of CKD is its a non-reversible and the function of the kidneys reduces progressive-ly. As the estimation of 24 hour urine protein levels is cumbersome, the current research aims to how valid is the use of the ration of Spot urine protein to creatinine in place of 24 hour method. Aims: To compare UPCR with urine protein for 24 hours with respect to the stages 3 and 4 of CKD. To validate UPCR for estimating proteinuria in the stages 3 and 4 of CKD. Study setting and study design: A comparative observational study among patients with the stages of 3 and 4 in CKD. Methods and Material: A total of 90 patients in stages 3 and 4 of CKD were chosen for the study. All the 90 patients were subjected to UPCR and protein in urine for 24 hours to check validity of UPCR in comparison to gold standard. Statistical analysis : The data analysis was done using SPSS. Significance tests: Chi-square and correlation. Results: A positive correlation was observed among the subjects with CKD for both the urine protein for 24 hours and UPCR .In the stage 3, UPCR was found to have lower sensitivity and specificity. Whereas UPCR had good sensitivity in diagnosing the stage. Conclusions: The present study showed UPCR to have good sensitivity and good specificity for CKD stage 4 than stage 3. Hence UPCR can be better indicator for CKD stage 4 than stage 3. Keywords: CKD, 24 hour urine protein, Urine protein creatinine ratio